LÆRERE, POLITIK OG PROFESSION DANMARK I 1960’ERNE OG 1970’ERNE - de Coninck-Smith, Ning (Temp - tidsskrift for historie, 2014)
ABSTRACT Teachers, Politics and Profession: Denmark in the 1960’s and 1970’s The focus of this article is the political mobilization of Danish teachers during the 1960’s culminating with a one-day strike in March 1973. As civil servants, the teachers were not allowed to strike, but a comment made by the Danish Minister of Finance Per Hækkerup on national television about teachers working too little and earning too much, sparked the political reaction. The strike hit schools across the whole country, and the article draws on memoirs and contemporary educational journals and reports in its discussion of why and how a self-conscious and critical approach towards the school system, teaching and teachers working conditions gradually seemed to become part of teachers understanding of their profession.